Peningkatan Efisensi Administrasi Usaha Melalui Tata Kelola Kearsipan Pada UMKM Ayam Petelur Rumahan - Qotrunada, Arifah Sitta; Kusumaningtias, Eka (JURNAL INOVASI HASIL PENGABDIAN (JIHAN), 2026)
The dynamics of micro, small, and medium enterprises (UMKM) are characterized by rapid product turnover. One such UMKM business is the staple food sector, namely eggs. The primary focus is often on production and sales. As a result, administrative aspects such as archive management, which includes recording invoices, supplier data, customer records, and transaction receipts, are often not optimally managed. More deeply, well-organized archives are a crucial foundation for a healthy business. Archive management is crucial for tracking cash flow, managing receivables, validating stock, and serving as evaluation material for strategic decision-making. Therefore, through this community service activity, we strive to provide practical guidance and training on an effective, efficient, and easy-to-implement archiving system. Our ultimate goal is for our partner UMKM to have a more orderly and structured administrative system.